THE CONTRIBUTION OF LEGISLATIVE AND FINANCIAL REGULATIONS TO THE SUCCESS OF PROFESSIONAL SPORTS IN ALGERIA - Ali Tebbani; Bachir Kerroum; Khaled Khadar (International Journal of Innovative Technologies in Social Science, 2025)
This article aims to highlight the role of legislative and financial regulations in the success of professional sports in Algeria, considering it a strategic option for developing national sports and enhancing its competitive level. The article addressed the legal framework governing professional sports, highlighting the importance of laws and regulations in organizing professional contracts, transforming clubs into legal entities, and ensuring the rights of various stakeholders in the sports system. It also addressed the financial requirements and their pivotal role in supporting professionalism, by providing stable funding sources, encouraging sports investment, and achieving financial sustainability for clubs. The article highlighted the existing integration between the legislative and financial aspects in achieving administrative and financial stability, improving the sports work environment, and enhancing competitiveness both locally and internationally. Moreover, it concluded that the success of professional sports in Algeria depends on the effective implementation of sports legislation and the development of financing and investment mechanisms, ensuring a genuine and sustainable professionalism that contributes to the development of sports performance and the achievement of comprehensive sports development.